PERLINDUNGAN HUKUM BAGI KONSUMEN DAN PRODUCT LIABILITY DALAM PRODUK MI INSTAN IMPOR BERSERTIFIKAT HALAL PALSU DI SEMARANG - Putra, Yana Arnanda; Triasih, Dharu; Septiandani, Dian (Semarang Law Review (SLR), 2022)
This scientific article talks about Fake halal-certified imported instant noodle products circulating in Semarang make Muslim consumers uneasy and concerns arise to buy these imported instant noodle products at minimarkets and E-Commerce. This study discusses Consumer Protection of imported instant noodle products that are certified halal fake in Semarang and the Implementation of Legal Protection for consumers and product liability in imported instant noodle products that are certified fake halal in Semarang. The methods used in this research include the type of research is empirical juridical, the research specifications are descriptive analytical. This research technique is non-random with purposive sampling and the data used are primary data in the form of interviews and questionnaires and supported by secondary data with qualitative data analysis. This research technique is non-random with purposive sampling and the data used are primary data in the form of interviews and questionnaires and supported by secondary data with qualitative data analysis. The form of legal protection for consumers is in the form of Law Number 8 of 1999 concerning Consumer Protection and Law Number 33 of 2014 concerning Halal Product Guarantees as well as supervision from BPJPH and MUI in carrying out the certification process of halal products and product liability or product liability for business actors in carrying out their functions as producers and importers of imported instant noodle products. In the implementation of the application of legal protection for consumers by carrying out policies and supervision in accordance with the authority regulated by the legislation. The right of consumers to obtain legal protection and obligations of business actors after obtaining a halal certificate has been regulated in the Halal Product Guarantee Law and the existence of administrative sanctions and criminal sanctions. And the implementation of the implementation policy of the Halal Product Guarantee Operator can be done with an awareness of responsibility in realizing security, safety and comfort.